2021
DOI: 10.1016/j.cjco.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Wedge Pressure vs Left Ventricular End-Diastolic Pressure for Pulmonary Hypertension Classification and Prognostication in Severe Aortic Stenosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A waiver of consent was granted. We have previously reported on other hemodynamic aspects in this population 9–14 …”
Section: Methodsmentioning
confidence: 89%
“…A waiver of consent was granted. We have previously reported on other hemodynamic aspects in this population 9–14 …”
Section: Methodsmentioning
confidence: 89%
“…Whether this is also the case in AS patients pre‐ and/or post‐AVR will have to be tested prospectively. Third, we and others have shown that mPAWP and LVEDP can differ substantially 28,29 . This can have impact of the haemodynamic classification of pulmonary hypertension where a few millimetres of mercury can be relevant around the cut‐off value of 15 mmHg 28 .…”
Section: Limitationsmentioning
confidence: 87%
“…Third, we and others have shown that mPAWP and LVEDP can differ substantially. 28 , 29 This can have impact of the haemodynamic classification of pulmonary hypertension where a few millimetres of mercury can be relevant around the cut‐off value of 15 mmHg. 28 Therefore, calculation of LVSWI based on mPAWP is not absolutely accurate.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been shown in a previous study [ 32 ] that patients with atrial fibrillation had higher PCWP than LVEDP values because of the absence of left atrial contraction. Maeder et al [ 33 ] showed in their collective of patients with severe AS and atrial fibrillation a small correlation between PCWP and LVEDP with r = 0.29. This is comparable to our weak regression analysis with an R = 0.216, an R 2 = 0.047 and a p = 0.061.…”
Section: Discussionmentioning
confidence: 99%